Outcome Comparison Between Tocilizumab and Pulse Solumedrol in Severe Covid Disease Among Resource Depleted Areas - Qasim Nawaz Sahi, Muhammad Ahmad, Mehwish Kiran, Arslan Iqbal, Arsalan Ahmad Khan Durrani, Hafiz Muhammad Rizwan, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Pandemic coronavirus disease 2019 (COVID-19) caused by SARS-CoV-2 coronavirus has recently emerged. Objectives: The main objective of the study is to find the outcome comparison between tocilizumab and pulse solumedrol in severe COVID disease among resource depleted areas. Material and methods: This cross sectional study was conducted in Central Park Medical College and Teaching Hospital, Lahore and the duration of this study was from August 2021 to March 2022. The data was collected through non-probability consecutive sampling technique. The data was collected into two groups. Men and non-pregnant women over 18 years old COVID diagnosis confirmed by real time polymerase chain reaction (RT-PCR) Pao2 / FIO2 <200 Laboratory: high sensitivity C reactive protein> 5 mg / L; lactic dehydrogenase (LDH ) > 245 U / l; Ferritin> 300; D-dimer> 1500; Interleukin-6> 7.0 pg / ml were included. Results: The data was collected from 300 patients, 150 in each group. There were 72.9% male aged 41–60 years 45.8% were female with a mean age of 55.4 ± 10.6 years. Diabetes and hypertension was the most common comorbidity in selected patients. Tocilizumab group had more number of males (P = 0.017), with higher incidence of coronary artery disease (CAD, P = 0.008). Conclusion: It is concluded that Tocilizumab decreased the propensity of severe COVID-19 patients to require invasive mechanical ventilation when compared to high-dose solumedrol pulse, especially in those with severe ARDS, but this did not translate to improved 30-day survival in them.